The Influence of Radiation on Unstable MHD Free Convection over a Vertical Plate in Two Dimensions - deleted (Al-Qadisiyah Journal of Pure Science, 2023)
This research studies the case of unsteady heat flux under the influence of two main factors: thermal radiation and magnetic force across a vertical plate. In order to explore the partial differential equations without introducing the dimensions of energy, momentum and continuity, a set of dimensionless nonlinear systems of partial differential equations were solved using the numerical finite difference method. Because of the assumed parameter ramifications of the velocity and temperature problem are also investigated without dependence on dimensions. Temperatures and momentum profiles are derived via finite differences. Following that, a qualitative and visual presentation of the parameter results on the velocity and temperature profiles is made .